Assessment of the Commitments and Performance of the European Food Industry to Improve Population Nutrition - Iris Van Dam; Iris Van Dam; Emilie Guillon; Ella Robinson; Olivier Allais; Gary Sacks; Stefanie Vandevijvere (Frontiers Media S.A., 2022)
Objectives: Food companies could play an important role in improving population diets, but often escape accountability through unspecific commitments. This study evaluated nutrition-related commitments and estimated performance of the largest packaged food and non-alcoholic beverage manufacturers, supermarkets and quick-service restaurants (QSR) in Europe.Methods: To quantitatively assess companies' publicly available commitments in 2020, the "Business Impact Assessment on Obesity and Population Nutrition" was applied. The proportion of sales from ultra-processed and "unhealthy" food categories (product categories not-permitted to be marketed to children) and over time changes in the number of QSR transactions and QSR and supermarket outlets were calculated.Results: Company commitments fell short of best practice recommendations (median overall score of 21%, range: 1%-62%). Food and beverage companies generated 82% (15%-100%) and 58% (1%-100%) sales from ultra-processed and "unhealthy" products, respectively. The number of QSR outlets and transactions substantially increased in Europe since 2011, while QSR commitments to improve population nutrition remained limited.Conclusion: Whilst most companies made some nutrition-related commitments, they did not comply with best practice recommendations. A large proportion of sales was generated from ultra-processed/unhealthy products and QSR outlets increased. Government regulations are urgently needed.